2020
DOI: 10.21613/gorm.2018.911
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Incontinence Severity on Symptom Distress, Quality of Life, and Pelvic Floor Muscle Function in Turkish Women with Urinary Incontinence

Abstract: <p><strong>Objective:</strong> The aim of the present study was to compare the differences in symptom distress, quality of life, and pelvic floor muscle function among Turkish women with mild, moderate, or severe urinary incontinence.</p><p><strong>Study design:</strong> One hundred and twenty women with a diagnosis of urinary incontinence (54.2% stress urinary incontinence and 45.8% mixed-urinary incontinence) participated in the present study. The severity of the uri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Moreover, Kamel et al [30] noticed that twelve weeks of abdominal muscle strength exercise was more effective in treating obese patients with SUi than PFMT. Another study, by Khan et al [31], found that women aged 30 to 45 with SUi improved significantly in SUi and QoL after performing the core muscles and PFMT for six weeks with five sessions per week.…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, Kamel et al [30] noticed that twelve weeks of abdominal muscle strength exercise was more effective in treating obese patients with SUi than PFMT. Another study, by Khan et al [31], found that women aged 30 to 45 with SUi improved significantly in SUi and QoL after performing the core muscles and PFMT for six weeks with five sessions per week.…”
Section: Discussionmentioning
confidence: 96%
“…Similar results were observed by Singh et al (2015) (17) who noted that half of study subjects have moderate urinary incontinence. Orhan C et al (2019) (18) studied the "Effect of incontinence severity on symptom distress, quality of life, and pelvic floor muscle function in Turkish women with urinary incontinence" reported that two-thirds of study subjects had mild and moderate degrees urinary incontinence. On the other hand, Kobashi (2011) (19) concluded that stress urinary incontinence generally considered majority of studied women were mild degree who only experience light leakage during vigorous activity such as playing sports or exercising, or while sneezing, laughing and coughing.…”
Section: Assessmentmentioning
confidence: 99%